Food that Builds Community: The Sikh Langar in Canada - Desjardins, Michel; Desjardins, Ellen (Cuizine)

(untitled) (McGill University Library, 2009)
AbstractThe communal meal, or langar, served in Sikh places of worship is central to Sikh religious thought and practice, both in India and in Canada. This paper introduces readers to the characteristics and principles embedded in Sikh langars, and to some distinctive Canadian elements of this food-centered marker of Sikh religious life, including internal community building and outreach activities. The authors incorporate data from their fieldwork, conducted in India and across Canada over the last three years.